GE_GERICHTE P/1174/2011 vom 30. Juni 2011 - GE Cour de justice (2011)
; ADOLESCENT ; AGRESSION ; ADMINISTRATION DES PREUVES ; COMPLÉMENT | PPMIN.3; PPMIN.20; PPMIN.30; CPP.319; CPP.397; DPMIN.1; CP.134; CP.126; CP.177